2020
DOI: 10.1016/j.foodres.2020.109802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant-rich propolis and bee pollen extracts against D-glucose induced type 2 diabetes in rats

Abstract: The present study was designed to investigate the preventive effect of propolis, bee pollen and their combination on Type 2 diabetes induced by D-glucose in rats. The study was carried out by feeding daily two concentrations (100 and 200 mg/Kg BW) of propolis or bee pollen (or their combination to normal (non-diabetic) and diabetic rats for a period of 16 weeks. In vivo biochemical changes associated to diabetes are induced by drinking a solution containing 10% of D-glucose (diabetic rats). The in vitro antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 66 publications
0
47
0
Order By: Relevance
“…The data illustrates that the intraperitoneal injections of gentamicin (120 mg/kg BW/day, i.p.) for 10 consecutive days lead to a significant increase of organs' relative weight in comparison with the normal group, and this goes in hand with the findings of Laaroussi et al [92]. The relative organ weight increase might be related to the inflammatory and oxidative stress effects of gentamicin overuse.…”
Section: Effect Of Interventions On Body and Organ Weightmentioning
confidence: 56%
“…The data illustrates that the intraperitoneal injections of gentamicin (120 mg/kg BW/day, i.p.) for 10 consecutive days lead to a significant increase of organs' relative weight in comparison with the normal group, and this goes in hand with the findings of Laaroussi et al [92]. The relative organ weight increase might be related to the inflammatory and oxidative stress effects of gentamicin overuse.…”
Section: Effect Of Interventions On Body and Organ Weightmentioning
confidence: 56%
“…e physicochemical properties of apple cider vinegar make it an ecologic solvent to extract bioactive compounds [27]. Recently, the combination of numerous natural products proved their efficiency to prevent and treat several pathologies such as diabetes, cardiovascular ailments, and oxidative stress [28][29][30][31]. e incorporation of natural products in daily diet constitutes the first line to prevent the installation of different diseases as dietary therapies [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in vivo studies have shown that Moroccan propolis exhibited a promising antidiabetic activity; it significantly decreased blood glucose level, increased insulin sensitivity and pancreatic β cell function, ameliorated dyslipidemia by the decrease of TC, TG, LDL-C, and VLDL and the increase of HDL, and prevented diabetic complications such as liver and kidney injury [18,19]. Other reports showed that Moroccan propolis has a strong antioxidant, antibacterial, anti-inflammatory, and anticancer potential [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%